The Prevalent Comorbidome at the Onset of Psoriasis Diagnosis - Alessandra Buja; Andrea Miatton; Claudia Cozzolino; Alessandra Rosalba Brazzale; Roberta Lo Bue; Santo Raffaele Mercuri; Fabian Nikolai Proft; Khalaf Kridin; Arnon Dov Cohen; Giovanni Damiani (Dermatology and Therapy, 2023)
Abstract Introduction Psoriasis (PsO) is currently regarded as a systemic inflammatory disease with a growing burden of post-diagnosis associated comorbidities. To determine the initial burden of comorbiditis we evaluated the comorbidome at PsO onset. Methods In a matched case–control study, we extracted data on 57,228 patients and 125 morbidities from the Clalit Health Services Israeli insurance database. PsO cases were matched with control individuals by sex and age at enrolment. As pre-existing comorbidities, we considered all conditions already present in controls at the same age as the matched PsO case at the time of their diagnosis. To test for differences in the odds of comorbidities between the case and control groups, logistic regression analyses were run to calculate the odds ratio (OR) for each comorbidity, after which the comorbidome was graphically represented. Results In this study we enrolled 28,614 PsO patients and 28,614 controls with an average age of 45.3 ± 19.6 years. At the time of diagnosis, PsO patients were more likely to be diagnosed with 2–4 comorbidities (28.8% vs 23.8%) and > 5 (19.6% vs 12.9%,). PsO patients’ specific comorbidomes evidenced several pathological cores: autoimmune and inflammatory systemic diseases [i.e., hidradenitis suppurativa (OR 3.55, 95% CI 1.88–7.28) or polymyalgia rheumatica (OR 3.01 95% CI 1.96–4.77)], inflammatory bowel diseases [i.e., Crohn’s disease (OR 2.99 95% CI 2.20–4.13)], pulmonary inflammatory diseases [i.e., chronic obstructive pulmonary disease (OR 1.81 95% CI 1.61–2.04)], hepatological diseases [i.e., cirrhosis (OR 2.00 95% CI 1.36–3.00)], endocrine diseases [dysthyroidisms (OR 1.82 95% CI 1.30–2.59)], mental disorders [i.e., depression (OR 1.72 95% CI 1.57–1.87)], and cardiovascular diseases (i.e., hypertension (OR 1.47 95% CI 1.41–1.53)]. Conclusion The PsO-onset comorbidome may help health professionals plan more comprehensive patient management. By screening for these common PsO-linked conditions, early diagnosis and treatment may become more frequent, thus greatly benefiting patients on their medical journey.